Research Trends in Problem-Based Learning: A Narrative Review of Studies on Students’ Engagement - Aryani Firiana; Tiyas Saputri; Nailul Authar; Mujad Didien Afandi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Problem-Based Learning (PBL) is widely recognized as an instructional approach that encourages active learning, critical thinking, collaboration, and meaningful student participation. Although many previous studies have examined the effectiveness of PBL in improving academic achievement, relatively fewer studies have specifically discussed how PBL influences students’ engagement throughout the learning process. Therefore, this study aims to analyze the development of research on PBL related to students’ engagement during the 2016–2025 period. This study applies a narrative review method by examining open-access journal articles that are relevant to the topic. The analysis focuses on research trends, methodological approaches, engagement dimensions, and key findings reported in previous studies. The findings show that research on PBL has increased over the last decade and has gradually shifted toward a broader discussion of students’ behavioral, emotional, and cognitive engagement. The most frequently used research methods include quasi-experimental design, classroom action research, and mixed-method approaches. Overall, PBL has been proven effective in increasing students’ active participation, learning motivation, collaboration, problem-solving ability, and conceptual understanding. However, several challenges remain in its implementation, including limited learning time, unequal student participation, teachers’ readiness, and the need for appropriate problem design. This review indicates that PBL is not only relevant for improving learning outcomes but also plays an important role in strengthening students’ engagement in the learning process. Future studies are recommended to explore PBL implementation across different educational levels, subjects, and learning contexts, especially in technology-supported, interdisciplinary, and inclusive classroom environments that require sustained participation and reflective learning over time.